Development and validation of an anisotropic damage constitutive model for C/SiC composite. Issue 18 (15th December 2018) - Yang, Qiang; Han, Xinxing; Xu, Chenghai; Xie, Weihua; Meng, Songhe
Abstract: Due to damage coupling and anisotropic evolution, constitutive models of Ceramic Matrix Composites are generally deficient in the description of material behavior under complex load conditions. This paper studied the mechanical behavior of a PIP prepared 3k carbon fabric plain woven C/SiC material under complex stress states. The phenomenon and mechanism of the anisotropy damage were analyzed. A constitutive model was proposed considering the anisotropy damage effect by load ratio functions, and only scalar damage variables were used to maintain a simple formulation. The constitutive model was validated against tensile tests of hat-shaped CMC components, and a FEM model of the experiments was established. The comparisons of strain results between the experiments and the FEM simulation showed good agreement under different loads. The model can be employed to facilitate structural analysis and design where material non-linearity is important.